Transplant Nephrectomy Improves Survival following a Failed Renal Allograft - Ayus, Juan Carlos (American Society of Nephrology, 2010)
There is a growing number of patients returning to dialysis after a failed kidney transplant, and there is increasing evidence of higher mortality among this population. Whether removal of the failed renal allograft affects survival while receiving long-term dialysis is not well understood. We identified all adults who received a kidney transplant and returned to long-term dialysis after renal allograft failure between January 1994 and December 2004 from the US Renal Data System. Among 10,951 transplant recipients who returned to long-term dialysis, 3451 (31.5%) received an allograft nephrectomy during follow-up. Overall, 34.6% of these patients died during follow-up. Receiving an allograft nephrectomy associated with a 32% lower adjusted relative risk for all-cause death (adjusted hazard ratio 0.68; 95% confidence interval 0.63 to 0.74) after adjustment for sociodemographic characteristics, comorbidity burden, donor characteristics, interim clinical conditions associated with receiving allograft nephrectomy, and propensity to receive an allograft nephrectomy. In conclusion, within a large, nationally representative sample of high-risk patients returning to long-term dialysis after failed kidney transplant, receipt of allograft nephrectomy independently associated with improved survival.